2014
DOI: 10.1111/febs.13159
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA biogenesis factor DRB1 is a phosphorylation target of mitogen activated protein kinase MPK3 in both rice and Arabidopsis

Abstract: MicroRNA (miRNA) biogenesis requires AtDRB1 (double-stranded RNA binding protein)/HYL1 (Hyponastic Leaves1) protein for processing and maturation of miRNA precursors. The AtDRB1/HYL1 protein associates with AtDCL1 (Dicer-Like1) and accurately processes primary-miRNAs (pri-mRNAs) first to precursor-miRNAs (pre-miRNAs) and finally to mature miRNAs. The dephosphorylation of AtDRB1/HYL1 protein is very important for the precise processing of miRNA precursors. The monocot model crop plant Oryza sativa encodes four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 31 publications
2
72
0
2
Order By: Relevance
“…After this initial complex is formed, HYL1 and RCF3 might join the complex, a step dependent on both proteins' phosphorylation status, and anchor the precursors by specific RNA and protein interactions (3,26). Both HYL1 and RCF3 are recruited to the complex in their hypophosphorylated isoforms: states that are reached due to the CPL1/2 phosphatase activity and antagonized by MPK3 (3,26,28). Localization experiments revealed that CPL1 activity is required for the correct localization of RCF3 and HYL1 (3,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After this initial complex is formed, HYL1 and RCF3 might join the complex, a step dependent on both proteins' phosphorylation status, and anchor the precursors by specific RNA and protein interactions (3,26). Both HYL1 and RCF3 are recruited to the complex in their hypophosphorylated isoforms: states that are reached due to the CPL1/2 phosphatase activity and antagonized by MPK3 (3,26,28). Localization experiments revealed that CPL1 activity is required for the correct localization of RCF3 and HYL1 (3,21).…”
Section: Discussionmentioning
confidence: 99%
“…The miRNA biogenesis cofactor HYL1 is subject to phosphorylation, which regulates its activity (3,28). HYL1 phosphorylation depends on CPL1, CPL2, and MITOGEN-ACTIVATED PROTEIN KINASE 3 (MPK3).…”
Section: Rcf3 Regulates Mirna Biogenesis Predominantly In Specific Plantmentioning
confidence: 99%
“…RNA extraction and Real time expression analysis was performed41. 2 −ΔΔC T values were calculated by method described in ref.…”
Section: Methodsmentioning
confidence: 99%
“…Protein modifications also regulate the activity of the DCL1 complex. For example, HYL1 activity is controlled by phosphorylation and dephosphorylation (30,31). Furthermore, the expression levels of the DCL1 complex are regulated at transcriptional and posttranscriptional levels to influence miRNA accumulation (32)(33)(34).…”
mentioning
confidence: 99%